1993
DOI: 10.1099/00221287-139-6-1301
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the accessory gene regulator (agr) in expression of type 5 capsular polysaccharide by Staphylococcus aureus

Abstract: The effect of an agr mutation on expression of type 5 capsular polysaccharide (CP) by Staphylococcus aureus Newman was investigated in different complex and synthetic media. CP expression by the agr mutant was strongly reduced in certain media but slightly in others, indicating that CP synthesis is positively controlled by agr. CP expression occurred in the post-exponential growth phase in both wild-type and mutant strains, suggesting that other regulatory systems could act in conjunction with agr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 51 publications
5
34
0
Order By: Relevance
“…Although capsule production is very important in the survival of S. aureus during different phases of infection, very little is known about the mechanism that regulates the cap operon. Several global regulators have been shown to affect the production of the capsule, indicating that several environmental and host signals must be integrated to fine-tune this process (Luong et al, , 2003(Luong et al, , 2011Luong & Lee, 2006;Chen et al, 2007;Dassy et al, 1993;Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although capsule production is very important in the survival of S. aureus during different phases of infection, very little is known about the mechanism that regulates the cap operon. Several global regulators have been shown to affect the production of the capsule, indicating that several environmental and host signals must be integrated to fine-tune this process (Luong et al, , 2003(Luong et al, , 2011Luong & Lee, 2006;Chen et al, 2007;Dassy et al, 1993;Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several global regulators have been shown to control the production of the capsule, including agr, sarA, arl and mgrA, as well as others (Luong et al, , 2003(Luong et al, , 2011Luong & Lee, 2006;Chen et al, 2007;Dassy et al, 1993;Gupta et al, 2013). A detailed analysis of the cap operon promoter has revealed that it is highly regulated (Ouyang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. aureus, type 5 capsule has been shown to be downregulated by agr, a global regulatory locus (Dassy et al, 1993). Both type 5 and 8 capsules have been shown to be affected by different growth conditions Dassy et al, 1991;Stringfellow et al, 1991;Mamo et al, 1987), suggesting that they are regulated.…”
Section: Discussionmentioning
confidence: 99%
“…One possible role of B in this scenario is to prolong the production of cell surface proteins, such as fibronectin binding proteins, that are positively influenced by SarA and negatively influenced by agr (55,60). Simultaneously, B may down-regulate RNAIII-specific activities, i.e., the repression of protein A and upregulation of exoproteins (36,49) or the production of capsular polysaccharides (22,51). Consistent with this hypothesis is our finding that the rsbU ϩ derivative GP268 possessed a significantly lower fibronectin-clumping titer than its rsbU-defective parent, BB255, signalling the presence of larger quantities of fibronectin binding proteins in GP268 than in BB255.…”
Section: Fig 8 Effect Of Overexpressedmentioning
confidence: 99%